2001
DOI: 10.1176/appi.ajp.158.8.1305
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind Comparative Study of Clozapine and Risperidone in the Management of Severe Chronic Schizophrenia

Abstract: Clozapine showed superior efficacy over risperidone in this patient population. Both treatments were equally well tolerated as demonstrated through their adverse event profiles, although as expected clozapine was associated with a lower risk of extrapyramidal symptoms than risperidone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
101
0
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(106 citation statements)
references
References 24 publications
0
101
0
5
Order By: Relevance
“…Controlled trials 76,[91][92][93] have generally failed to confirm the promise of benefit in treatmentresistant schizophrenia seen in early, uncontrolled studies. For example, Wirshing and colleagues 94 compared risperidone and haloperidol in a sample of 67 subjects with treatment-resistant schizophrenia.…”
Section: Risperidonementioning
confidence: 99%
See 1 more Smart Citation
“…Controlled trials 76,[91][92][93] have generally failed to confirm the promise of benefit in treatmentresistant schizophrenia seen in early, uncontrolled studies. For example, Wirshing and colleagues 94 compared risperidone and haloperidol in a sample of 67 subjects with treatment-resistant schizophrenia.…”
Section: Risperidonementioning
confidence: 99%
“…Azorin and colleagues 91 noted the methodological problems with such comparative studies of risperidone and clozapine, such as small sample sizes and the use of suboptimal clozapine doses. They sought to remedy such deficiencies in their own prospective, double-blind study.…”
Section: Risperidonementioning
confidence: 99%
“…These mice maintain large distances from wild-type littermates and actively avoid social investigation when used as the residents in a resident-intruder paradigm (Mohn et al, 1999). In both chronic PCP treated animals and the NR1 knockdown mice, the atypical antipsychotic drug, clozapine, which appears to treat negative symptoms and social deficit symptoms better than other treatments (Azorin et al, 2001;Buchanan et al, 1998), improves sociality. On the other hand, the typical antipsychotic drug, haloperidol, is inactive (Sams-Dodd, 1997;Qiao et al, 2001, Mohn et al, 1999.…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated that clozapine is superior to other atypical antipsychotics as well as the typical antipsychotics (McEvoy et al, 2006). Older studies showed that clozapine is one of the most effective oral atypical antipsychotics due to 1) superior improvement in positive and negative symptoms, 2) efficacy in the treatment of refractory schizophrenia, and 3) reduction in patient suicide risk (Reid et al, 1998, Volvavka et al, 2002, Azorin et al 2001, Buchanan et al, 1998. Even when observational studies are considered, as opposed to clinical trials, clozapine has been shown to have superior efficacy (Brambilla et al 2002) particularly with refractory patients.…”
Section: Introductionmentioning
confidence: 82%